TREN KEJADIAN KERACUNAN MAKANAN DIBERBAGAI WILAYAH DI INDONESIA TAHUN 2014 DAN TAHUN 2015 - Muslikha Nourma Rhomadhoni; Nurul Jannatul Firdausi; Novera Herdiani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
Food poisoning is a condition that arises from consuming foods that contain toxins, for example: mushrooms, shellfish, pesticides, milk, toxic materials due to food and bacteria decomposition. WHO reports that approximately 70% of diarrhea cases in developing countries are caused by contaminated food that is mostly from food in catering and restaurant. In the United States poisoning cases occur in 20% in restaurants, 3% in the food industry. In Europe the source of contamination is 46% from home, restaurant / hotel (15%), 8% banquet, health facility and canteen respectively 6% and school 5%. Incidence of risk of poisoning increased due to microbial factors, host factors and factors related to diet. In Indonesia through the Drug and Food Control Agency (BPOM) has been inventoried poisoning events through online news in one year. This study aims to determine the trend of food poisoning incidence in various regions in Indonesia 2014 and 2015. By identifying the number of food poisoning events in 2014, identify the causes of poisoning events in 2014, identify the number of incidents of food poisoning in 2015, identify the causes of poisoning events in 2015, Analyzing the trend of food poisoning events in 2014 and 2015. Toxicity identification results in 2014 contained 186 total occurrences. The 2015 poisoning identification results contained 153 total incidents, with various causal factors, ranging from food, natural toxins, pesticides, mixtures, and environmental pollution. Incidence of poisoning in 2014-2015 decreased 28% in one year. In 2014 there were a total of 186 events and by 2015 there were a total of 153 events.